The Effect of Customers' Price Perception, Perceived Quality and Brand Image Toward Purchasing Intention in Bandung Local Shoe Brand - Ika Septiani , Dini; Chaerudin, Rendra (KnE Social Sciences, 2020)
Despite the contribution of shoe industry for Indonesia economic growth most of the entrepreneur has a problem to scale up their business. Intense competition becomes one of the reasons. In order to capture the current market, a company should concern to determine consumer purchase intention. However, customers purchase intention is a complex process. It is known that customers’ perceived quality, price perception, and brand image are factors that influence the purchasing intention of the product. The absence of owner knowledge in customer perception toward the brand indicates to cause the low of customer intention to buy the product. For this reason, the researcher interest to do research about the relationship between customer perception and purchasing intention. This study aims to discuss the effects of customers’ perceived quality, price perception, and brand image on purchase intentions toward shoe brand in Bandung, Jakarta, and Yogyakarta. This research using descriptive analytics and multiple linear regression to analyze the data collected. The research using non-probability sampling data collection technique with female respondents domiciled in Bandung, Jakarta, and Yogyakarta. The results of this study show that customers’ perceived quality, price perception, and brand image has a significant result on purchase intentions in the shoe brand. Furthermore, based on the results of this paper the researcher gives advice for the reference of future studies. Keywords: purchasing intention, perceived quality, price perception, brand image, perception.